Effective and Efficient Correction of Severe Skeletal Class II Division 1 Malocclusion with Intermaxillary Elastics - Mohammed K. Badri (Case Reports in Dentistry)
Treatment of Class II malocclusion accompanied with a skeletal discrepancy is challenging. The approach of correction depends on several factors such as the status and pattern of growth, severity of the malocclusion, and patient cooperation. This case report describes a successful management of a 12-year-old young adolescent boy that was presented with a Class II division 1 malocclusion with an underlying skeletal discrepancy in horizontal and vertical dimensions. Growth modification was achieved by means of bite opening and unlocking the mandible together with Class II elastics and mechanics. Treatment was highly effective and efficient by achieving all treatment goals within a period of 18 months.